Choosing nasal devices: a dilemma in clinical practice - Varricchio, Attilio; Brunese, Francesco; La Mantia, Ignazio; Ascione, Enrico; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Upper airway diseases are frequent and recognize different etiopathogenetic mechanisms, including infection, inflammation, and allergy. Therefore, topical treatments are preferable in comparison with systemic medications. Several delivery devices are available on the market, including nasal drops, syringes, sprays, nebulizers, and douches. However, it is clinically relevant to know the better way to use it. Methods: The present experience compared five different devices that were tested: i) a nasal dropper, ii) a standard nasal spray device, iii) a mucosal atomization device with a nozzle tip, iv) a nebulizer device, and v) a nasal douche. Saline solution with methylene blue was the marker to evaluate the intranasal distribution. Results: The findings showed an apparent difference in area distribution among these delivery devices. Conclusion The present experience showed that doctors should choose the most appropriate device for the current disease in clinical practice.